#Modaquetransforma e #Roupaviva: as hashtags que remetem aos pilares da sustentabilidade na comunicação digital das empresas de fast fashion e slow fashion no Brasil - Rios, Marina Pereira (2021)
The relationships between fashion, sustainability and digital communication are objects of study in order to understand some of the multiple working criteria of the media and companies today. Online media have significant visibility and influence to convey messages and content across their platforms. The research presented here seeks to analyze the content on the pillars of sustainability in online communication on the Instagram social network, developed by the companies Riachuelo and Flávia Aranha belonging to the fast fashion and slow fashion production systems. For this analysis to be possible, publications on the social network of companies that were related to this theme were selected during a one and a half year (from January 2020 to June 2021). As a theoretical apparatus, discussions on consumption and fashion with authors such as McCracken (2003), Calanca (2008), Miranda (2008), Miller (2013) and Cietta (2017) were taken into account, the concepts of sustainability and its relationship with fashion by Fletcher and Grose (2011), Salcedo (2014), Gwilt (2014) and Weetman (2019), the pillars of sustainability with Elkington (1994) and social networks such as Recuero (2009) and Musse (2017). Through Bardin's Content Analysis (1977), posts were clipped on the Instagram social network of companies that addressed the topic of sustainability in fashion. This analysis identified the expansion of discussions on the concept of sustainability beyond just the environmental point of view, focusing only on "greener products", expanding the discussions on production processes and social issues that involve these themes both with their employees and consumers. KEYWORDS: Fashion, Sustainability, Digital communication, Fast fashion, Slow fashion.